ASUPAN VITAMIN B12 TERHADAP ANEMIA MEGALOBLASTIK PADA VEGETARIAN DI VIHARA MEITRIYA KHIRTI PALEMBANG: ASUPAN VITAMIN B12 TERHADAP ANEMIA MEGALOBLASTIK PADA VEGETARIAN DI VIHARA MEITRIYA KHIRTI PALEMBANG - Muhammad Ridho Nugroho; Ratu Ayu Dewi Sartika (STIKes Hang Tuah Pekanbaru, 2018)
Nowadays more and more people are consciously diverting their eating habits from main foods consisting of meat into meatless foods consisting of various types of vegetables, nuts, seeds, grains and fruits that do not contain vitamin B12. Vitamin B12 is not absorbed in the colon, so strict vegetarianism always results in vitamin B12 deficiency which lasts very slowly in years. This study aims to determine the relationship of vitamin B12 intake to Megaloblastic Anemia in vegetarians at Meitriya Khirti Palembang Temple using a cross sectional design. From the results of research conducted using correlation tests obtained results that there is a relationship between intake of vitamin B12 with a mean value = 0.982 against the mean value of Corpuscular Volume (MCV) in vegetarian blood with a value of p = 0.037